Role of astroglial ACBP in energy metabolism flexibility and feeding responses to metabolic challenges in male mice. (5th December 2022) - Bouyakdan, Khalil; Manceau, Romane; Robb, Josephine L.; Rodaros, Demetra; Fulton, Stephanie; Alquier, Thierry
Abstract: Acyl‐CoA binding protein (ACBP), also known as diazepam binding inhibitor (DBI), has recently emerged as a hypothalamic and brainstem gliopeptide regulating energy balance. Previous work has shown that the ACBP‐derived octadecaneuropeptide exerts strong anorectic action via proopiomelanocortin (POMC) neuron activation and the melanocortin‐4 receptor. Importantly, targeted ACBP loss‐of‐function in astrocytes promotes hyperphagia and diet‐induced obesity while its overexpression in arcuate astrocytes reduces feeding and body weight. Despite this knowledge, the role of astroglial ACBP in adaptive feeding and metabolic responses to acute metabolic challenges has not been investigated. Using different paradigms, we found that ACBP deletion in glial fibrillary acidic protein (GFAP)‐positive astrocytes does not affect weight loss when obese male mice are transitioned from a high fat diet to a chow diet, nor metabolic parameters in mice fed with a normal chow diet (e.g., energy expenditure, body temperature) during fasting, cold exposure and at thermoneutrality. In contrast, astroglial ACBP deletion impairs meal pattern and feeding responses during refeeding after a fast and during cold exposure, thereby showing that ACBP is required to stimulate feeding in states of increased energy demand. These findings challenge the general view that astroglial ACBP exerts anorectic effects and suggest that regulation of feeding by ACBP is dependent on metabolic status. Abstract : ACBP deletion in GFAP positive astrocytes of male mice increases the susceptibility to diet‐induced obesity by promoting hyperphagia, without affecting weight loss when these obese mice are transitioned from a high fat diet to a chow diet. In contrast, astroglial ACBP deletion impairs meal pattern and reduces food intake during refeeding after a fast and during cold exposure, thereby showing that ACBP is required to stimulate feeding during or following states of increased energy demand. These results challenge the general view that astroglial ACBP exerts anorectic effects and provide a new framework in which the role of ACBP on feeding behavior is dependent on the metabolic status.